AN ANALYSIS OF TEACHERS’ PRACTICE IN USING AUTHENTIC MATERIAL FOR THE 8th GRADE STUDENTS AT SMPN 1 BLANGPIDIE ACEH BARAT DAYA - Hilma, Wardiatul; Moetia, Meristika (FKIP Unismuh Makassar, 2024)
This research was conducted to investigated the way teachers teach and apply the lesson using authentic materials in learning reading at SMPN 1 Blangpidie Aceh Barat Daya. This research was also influenced by the background of students who have just learned English in junior high school, that make English as a language is difficult for them. This research used descriptive qualitative as the research method. The instruments used to collect data are classroom observations and interviews. Data analysis in this study is analysis Data Reduction, Data Display and draw conclusions. The results showed that the teachers have carried out differentiated learning using authentic materials. Authentic materials in the classroom is derived from genuine exposure to real-world sources. In the development of reading using authentic material, the material sources in reading lessons that teachers most often use are newspapers, articles and social media, updated and accessed via the internet. In Conclusion, using authentic material improves students' reading translation skills, vocabulary, pronunciation, and motivation to learn English in the classroom at SMPN 1 Blangpidie Aceh Barat Daya.